Basque Boys Training Committee (statement) (1939)
1939 038-0082-004 - 2 - WHAT YOU CAN DO. 1. Help us to find openings for the boys in industry as apprentices or trainees, and watch over their interests when they have been placed in work. 2. Persuade your Trade Union Branch or Shop Committee to adopt a boy for a period of from one month to a year (he will require from 2s.6d. to 10s. a week to supplement his earnings during the first two or three years). Or form groups of friends. 3. Obtain offers of hospitality for the boys who are working. We can guarantee 15s. a week towards their keep until they are able to support themselves. 4. Finally, we are always in need of subscriptions and donations, large or small, and presents of clothes, shoes, sports equipment, text-books and magazines. The Committee responsible for these boys is a representative one, including among its members :- Robert Willis (Chairman) (Secretary of the London Trades Council) Dr. L. Haden Guest M.P. Mrs. Leah Manning (President of the National Union of Labour Teachers). Alderman Joseph Reeves (Educational Executive Committee of the Co-operative Union). Dr. Richard Ellis (National Joint Committee for Spanish Relief) . The fathers of these boys made a heroic stand in the Spanish people's struggle for freedom. Those of them who are alive today face a future of terrible hardship and uncertainty. Will you acknowledge their heroism by joining with us now in building up a happier future for their sons? Please send offers of help, or write for further information to the Secretary, Miss Molly Garrett, at 30, Eccleston Street, London, S.W.1. 292/946/38/82(IV)